Analisis Kriminologis Terhadap Penyalahgunaan Wewenang dan Modus Operandi Korupsi Dana Desa: Studi Kasus PJ Kepala Desa Sukadame, Kabupaten Labuhanbatu Selatan - Saribu, Marcella Camelia Putri Dolok; Yusuf, Hudi (Media Hukum Indonesia (MHI), 2025)
This study criminologically examines the abuse of authority and modus operandi of village fund corruption allegedly committed by the Acting Head of Sukadame Village, Silangkitang District, South Labuhanbatu Regency, North Sumatra. The suspect with the initials S alias SKM (45), a State Civil Apparatus and former Acting Village Head for the 2019–2021 period, was on the Wanted List (DPO) for two years since July 2023 before finally surrendering to the South Labuhanbatu Police on July 2, 2025. The results of the local Inspectorate audit recorded a total state loss of IDR 505,213,409 related to the 2020–2021 Sukadame Village budget.